Virtual Reality (VR) and Augmented Reality (AR) in Medicine: A Review of Clinical Applications - Collins Nwannebuike Nwokedi; Olakunle Saheed Soyege; Obe Destiny Balogu; Ashiata Yetunde Mustapha; Busayo Olamide Tomoh; Akachukwu Obianuju Mbata; Dorothy Ruth Iguma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This paper reviews the clinical applications of Virtual Reality (VR) and Augmented Reality (AR) in medicine, highlighting their transformative potential across surgical training, patient rehabilitation, diagnostics, psychological treatment, and medical education. Through an exploration of current applications and benefits, including improved training efficiency, enhanced patient care, and innovative diagnostic and treatment options, the paper underscores the significant impact of VR and AR technologies on healthcare delivery and patient outcomes. Challenges such as technical limitations, accessibility, cost, and privacy concerns are discussed, along with strategies to overcome these barriers. The paper concludes with recommendations for future research to advance the use of VR and AR in healthcare, emphasizing the need for cost-effective solutions, expanded clinical applications, and studies on long-term impacts. This review illustrates the promising future of VR and AR in enhancing clinical practice and patient care, advocating for continued innovation and research in this dynamic field.
Keywords: Virtual Reality; Augmented Reality; Clinical Applications; Healthcare Technology; Medical Education; Patient Rehabilitation